2021
DOI: 10.1186/s12993-021-00181-1
|View full text |Cite
|
Sign up to set email alerts
|

The mystery of claustral neural circuits and recent updates on its role in neurodegenerative pathology

Abstract: Introduction The claustrum is a structure involved in formation of several cortical and subcortical neural microcircuits which may be involved in such functions as conscious sensations and rewarding behavior. The claustrum is regarded as a multi-modal information processing network. Pathology of the claustrum is seen in certain neurological disorders. To date, there are not enough comprehensive studies that contain accurate information regarding involvement of the claustrum in development of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…It may work to integrate information from its connections with the mPFC, medial-dorsal thalamus, and BLA to focus attention and coordinate responses of its output structures such as the motor and sensory cortex (Smith et al, 2019 ). The claustrum has been linked to a number of disorders including AD, depression, and Parkinson’s disease (PD; Nikolenko et al, 2021 ). The insular cortex is another well connected brain region that has been shown to have numerous functions including processing of visceral sensations, somatosensory, pain, auditory, taste, experiencing of emotions such as disgust, sadness and happiness, empathy as well as cognitive processes such as decision making and attention (Uddin et al, 2017 ; Evrard, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It may work to integrate information from its connections with the mPFC, medial-dorsal thalamus, and BLA to focus attention and coordinate responses of its output structures such as the motor and sensory cortex (Smith et al, 2019 ). The claustrum has been linked to a number of disorders including AD, depression, and Parkinson’s disease (PD; Nikolenko et al, 2021 ). The insular cortex is another well connected brain region that has been shown to have numerous functions including processing of visceral sensations, somatosensory, pain, auditory, taste, experiencing of emotions such as disgust, sadness and happiness, empathy as well as cognitive processes such as decision making and attention (Uddin et al, 2017 ; Evrard, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The claustrum receives large numbers of inputs from numerous brain regions, including the parietal and medial temporal regions, and projects to the insula and frontal pole (Burman et al, 2011 ; Torgerson et al, 2015 ). Claustrum dysfunction has thus been linked to disruption in episodic memory formation (Schwindt & Black, 2009 ), attentional management (Atlan et al, 2018 ), consciousness (Koubeissi et al, 2014 ), cognitive functions (Krimmel et al, 2019 ), spatial navigation (Jankowski & O'Mara, 2015 ), and mechanisms of information processing across sensory modalities (Nikolenko et al, 2021 ), sexual functions (Redouté et al, 2000 ), and esthetic judgment (Ishizu & Zeki, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed significant volume decrease in AD compared with HC. A decreased volume of the claustrum is also associated with the presence of delirium, progression of dementia, and cognitive decline (Nikolenko et al, 2021 ). Abnormalities of the claustrum and insula have also been linked to the presence of positive symptoms in both neurodegenerative and psychiatric conditions (Venneri & Shanks, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identified a myriad of brain areas that are involved in AD development, such as the prefrontal cortex (PFC), entorhinal cortex (EC), and hippocampus. While recently, a nucleus located in the forebrain named claustrum (CLA), has gained increasing popularity due to its functions in attention, executive function and memory (Smith et al, 2020;Nikolenko et al, 2021;Whalley, 2022), which are perceived as an integral part of AD cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%